Implementation of Reinganum's Investment Strategy in Long Term Equity Fund in the Stock Exchange of Thailand - Panyagometh, Kamphol (International Journal of Economics and Financial Issues, 2017)
This research tested the investment strategy of Reinganum, which used value factors, momentum factors and size factors in the Stock Exchange of Thailand (SET) from 2002-2016. The results showed that value and momentum factors were able to excellently provide above-the-market returns, whiles size factors produced the opposite outcome. In addition, the aforementioned research findings were expanded upon by implementing Reinganum's investment strategy with Long Term Equity Fund (LTF). Keywords: Investment Strategy, Portfolio Management, Trading Strategy JEL Classifications: G11, G12